2020
DOI: 10.1039/c9ra08780j
|View full text |Cite
|
Sign up to set email alerts
|

Highly active Ce, Y, La-modified Cu/SiO2 catalysts for hydrogenation of methyl acetate to ethanol

Abstract: Highly active and stable La-modified Cu/SiO2 catalysts were fabricated for the vapor-phase hydrogenation of methyl acetate to ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Zhu et al discovered that the introduction of B 2 O 3 to Cu/SiO 2 could greatly promote the dispersion of Cu species by inhibiting the growth of Cu particles, which could enhance catalytic stability [21]. He et al reported that B-Cu/SiO 2 catalysts exhibit excellent catalytic stability, which was mainly resulting from the strong interaction between B 2 O 3 and surface Cu element, which maintained the suitable Cu 0 /Cu + distribution and restrained the growth of Cu particles [24]. As shown in Table S3, the change in the D Cu of 2B-Cu/SiO 2 catalyst was basically negligible and only dropped from 21.6% to 20.4%.…”
Section: Structure-performance Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al discovered that the introduction of B 2 O 3 to Cu/SiO 2 could greatly promote the dispersion of Cu species by inhibiting the growth of Cu particles, which could enhance catalytic stability [21]. He et al reported that B-Cu/SiO 2 catalysts exhibit excellent catalytic stability, which was mainly resulting from the strong interaction between B 2 O 3 and surface Cu element, which maintained the suitable Cu 0 /Cu + distribution and restrained the growth of Cu particles [24]. As shown in Table S3, the change in the D Cu of 2B-Cu/SiO 2 catalyst was basically negligible and only dropped from 21.6% to 20.4%.…”
Section: Structure-performance Relationshipmentioning
confidence: 99%
“…Ren et al have introduced La promoter into Cu/SiO 2 catalysts by hydrolysis precipitation method, which showed the outstanding catalytic performance with the Sel. EtOH of 95.8% at 250 • C [24]. However, there are still huge challenges need to be overcome, especially in terms of their poor low-temperature catalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth elements, such as Ce, Y or La, were used by Ren et al , to promote Cu/SiO 2 catalysts for MA hydrogenation. 296 They also prepared a La-modified copper phyllosilicate nanotube (Cu-PSNT) catalyst. 297 As a result, they found that the La addition can significantly influence the Cu dispersion and the ratio of Cu + /(Cu + + Cu 0 ), and increase the activity and stability of MA hydrogenation.…”
Section: Methanol/dimethyl Ether Carbonylation Followed By Hydrogenationmentioning
confidence: 99%
“…[18][19][20] Secondly, according to the literature, the catalyst life of the Cu-based catalysts for the hydrogenation of acetates in fixed-bed reactors was also very limited. [17,22,23] Most important of all, the hydrogenation of CHA to produce CHOL is a relatively new reaction route and would be very meaningful. Thence, Cu-based catalysts with enhanced catalytic performance including high CHA conversion, high CHOL selectivity and long lifespan were explored based on our previous researches.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the intrinsic ability of the catalysts needs to be further improved because in some cases the conversion or selectivity was below 90 % [18–20] . Secondly, according to the literature, the catalyst life of the Cu‐based catalysts for the hydrogenation of acetates in fixed‐bed reactors was also very limited [17,22,23] . Most important of all, the hydrogenation of CHA to produce CHOL is a relatively new reaction route and would be very meaningful.…”
Section: Introductionmentioning
confidence: 99%